Archipelago Islamic Art and Culture Perspective of Myths and Legends - Ahmad Syaikhu; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
Talking about myths and legends can hardly be separated from beliefs held since pre-historic times. Therefore, in the life of Indonesian people in the past, living in harmony with the universe was a priority in itself, where humans were able to place themselves in the whole in harmony, as seen in the story of Murwakala or the myth of origins. In this myth, there are various virtues that were used as guidelines for life by the people of the archipelago in the past so that they could live in harmony with nature, from waking up until the sun sets over the western horizon. There are various beliefs that exist in Indonesian society (especially Java). In fact, before Hindu-Buddhist religion touched the island of Java, the people who inhabited this island had long been familiar with various kinds of beliefs. Where the beliefs of the Indonesian people are closely tied to the myths and legends that develop and color those beliefs. One of the beliefs of the ancestors of the people of the archipelago, especially Java, is the belief in animism and dynamism. These two beliefs were already entrenched in Java. This is as stated by Zoetmulder, who said that Javanese people have known religion since prehistoric times. On the occasion of this paper assignment, the author tries to discuss Indonesian Islamic art and culture from the perspective of myths and legends, where in the lecture delivered by Dr. Zastro Al-Ngatawi more or less explains that actually in the archipelago in pre-historic times, the archipelago had long been inhabited by ancient humans who were inclined and able to seek the Almighty Essence, but with limitations and the absence of revealed religious guidance, humans manifested a sense of servitude and respect for very simple things such as the belief in animism and dynamism or what is called the kapitayan religion, where with this belief forms of art and culture were born that were created by preliterate humans, this is proven by the discovery of paintings on cave walls and corals which are thought to come from a period of advanced hunting and food gathering. These preliterate paintings are spread across a number of regions, such as South Sulawesi, Maluku and Papua. For example, on the wall of the Leang Patae Cave in South Sulawesi, a painting of a handprint with a red base was found, which is thought to be a symbol of protection from evil spirits. The paintings of ancient people on the walls of the caves and rocks that were found contain religious and aesthetic values. The existence of these paintings is initial evidence that preliterate society also had a passion for art. These paintings are a means of inheriting the past containing the experiences of prehistoric society such as hunting and social life. Because they did not know writing, these paintings are a historical tradition that has been passed down to future generations. During the farming and farming period, the artistic desires of the pre-literate people increased because during this period there was a lot of free time that could be used to channel their artistic creations. When planting time is over, they usually have quite a long time to wait for the harvest to arrive. While waiting for the harvest, the Praliterate community channeled their artistic desires. For example, painting, decorating metal items, sculpting, batik, weaving and making statues. The description of the belief system of the people of the prehistoric archipelago, apart from being known from the paintings on cave walls and coral reefs, can also be known from the procedures for burial ceremonies for their corpses. From the burial procedures, it can be seen that some of the bodies were sprinkled with red paint. It is suspected that the red paint is related to a burial ceremony to provide new life in the afterlife. Evidence of this burial procedure has been found in Lawa cave (Sampung area, Ponorogo), and in Sodong cave and on Shell Hill in North Sumatra. Evidence of burials during the hunting period proves that at that time there were certain assumptions about death. Ancient humans thought that people who had died would move to the afterlife, but could still have contact with people who were still alive. The existence of this belief encourages efforts to continue to respect the person who has died in the form of respect for his soul or spirit. From the description above, the author observes that the strong animist and dynamism beliefs held by the people of the archipelago at that time were due to the power of religious spirituality they possessed. However, the absence of revealed religious guidance has resulted in their powers of reason only being limited to their abilities, so that a simple artistic desire was born through paintings on cave walls and corals, religious ceremonies for the worship and respect of ancestral spirits with the values contained in them. inside. So, art and culture in the archipelago were born from the most basic source, namely strong spirituality and religion supported by the creativity of the people of the archipelago, which then formed myths and legends that developed and in their development were greatly influenced by Hinduism, Buddhism and Islam. Thus, art and culture were born that were unique and different from others.